Pengaruh Model Project Based Learning melalui Metode Praktikum terhadap Kemampuan Berpikir Kreatif pada Materi Getaran Harmonis Siswa Kelas XI MIA SMA Negeri 1 Comal - Khanifah Khanifah; Joko Saefan (Universitas PGRI Semarang, 2016)
Physics learning will give optimal learning outcomes if the students can buildknowledge and find the answer of a problem through the learning process which has beendone. Separately, some studies show that students lack of creative thinking ability andscientific works. Therefore, it needs project based learning model which can sharpen thestudents creative thinking ability to learn Physics.This experimental study aimed to know theeffects of Project Based Learning model through the method of laboratory working on thecreative thinking ability on the material of harmonic vibration at grade XI MIA of SMAN 1Comal. The samples of this study were Class XI MIA 2 as the experimental class and Class XIMIA 3 as the control class. The techniques used to gather the data in this study weredocumentation, observation, and tests.Based on the analysis of the hypotheses using one-tailed t-test with right side, the results showed that the was 2,99 and the was 1,67. Itcould be seen that the was higher than the so that the Ha was acceptedisaccepted. Meanwhile, from the gain test, it was obtained that the of experimental class was0.710 with high category and the of control class was 0.611 with medium category.The learning using Project Based Learning model through the method of laboratory working on thematerial of Harmonic Vibration at Grade XI MIA of SMAN 1 Comal gives effects on thecreative thinking ability and can develop the students’ creative thinking ability. Keywords: Creative Thinking Ability, Practicum Methods, Project Based Learning.